Protecting Antarctic blue carbon: as marine ice retreats can the law fill the gap? - Gogarty, B; McGee, J; Barnes, DKA; Sands, CJ; Bax, N; Haward, M; Downey, R; Moreau, C; Moreno, B; Held, C; Paulsen, ML (Climate Policy, 2019)
As marine-ice around Antarctica retracts, a vast blue carbon sink, in the form of livingbiomass, is emerging. Properly protected and promoted Antarctic blue carbon willform the worlds largest natural negative feedback on climate change. However,fulfilling this promise may be challenging, given the uniqueness of the region andthe legal systems that govern it. In this interdisciplinary study, we explain: theglobal significance of Antarctic blue carbon to international carbon mitigationefforts; the urgent need for international legal protections for areas where it isemerging; and the hurdles that need to be overcome to realize those goals. Inorder to progress conservation efforts past political blockages we recommend thedevelopment of an inter-instrument governance framework that quantifies thesequestration value of Antarctic blue carbon for attribution to states climatemitigation commitments under the 2015 Paris Agreement.